Ratoon Systems in Tidal Lowland: Study of Groundwater Dynamics and the Change of Nutrient Status on Rice Growth - Momon Sodik Imanudin; Bakri Bakri; Raina Jelita (Universitas Sebelas Maret, 2018)
It has been widely known that crop cultivation in tidal lowland areas in the second crop (March-April) is not conducted by farmers in a maximum way. Thus, this research aims at investigating the dynamics of groundwater and its nutrient status condition for the purpose of supporting plant cultivation in the second crop after rice planting. The study was conducted in Banyu Urip Village, Tanjung Lago Telang II, Banyuasin. The plant used in this activity was paddy, with the treatment of a ratoon cultivation system. The ratoon system is paddy cultivation by using the first paddy planting season shoots. A urea treatment was given with a dose of 0 kg/ha (control) and a dose of 150 kg/ha. The results of soil analysis showed that, although not significant, there was an increase in the nutrient status of the soil condition. Therefore, it can be concluded that fertilizing was considered ineffective for the system of ratoon cultivation. The study of groundwater dynamics showed that at the early phase, a groundwater table was dropped above 30 cm (critical) but it could increase by the rain and water retention in the canal. The average of the groundwater table during the ratoon period was at the depth of 5-30 cm below the soil surface, allowing it to be suitable for plant growth. The plant growth at B treatment was better and its production was 2.8 ton/ha. This 2.8 ton/ha plant production was classified as a high category for paddy with the ratoon cultivation system. There is no effect of the fertilizer treatment on the nutrient status in the soil. Moreover, the application of fertilizer did not give a significant result on the production of rice.